Reproductive Outcomes After Gestational Trophoblastic Neoplasia. A Comparison Between Single-Agent and Multiagent Chemotherapy: Retrospective Analysis From the MITO-9 Group. Issue 2 (February 2018) - Cioffi, Raffaella; Bergamini, Alice; Gadducci, Angiolo; Cormio, Gennaro; Giorgione, Veronica; Petrone, Micaela; Rabaiotti, Emanuela; Pella, Francesca; Candiani, Massimo; Mangili, Giorgia
Abstract : Objectives: Gestational trophoblastic neoplasia affects women of reproductive age and is usually treated by chemotherapy. Major concerns related to chemotherapy in young women are the possible infertility, risk of early menopause, and teratogenic effects on subsequent pregnancies. The study's aim was to analyze menstrual and reproductive outcomes of women treated with single-agent versus multiagent chemotherapy for gestational trophoblastic neoplasia. Methods: One-hundred fifty-one patients were treated. Seventy-six patients older than 45 years, with a placental site or epithelioid trophoblastic tumor, undergoing hysterectomy for patient choice, or undergoing human chorionic gonadotropin follow-up at the time of the analysis were excluded. Seventy-five patients were divided into subgroups according to International Federation of Gynecology and Obstetrics score: patients scoring less than 7, receiving single-agent chemotherapy (group A, n = 42); patients scoring 7 or greater, receiving combination treatment (group B, n = 33). Patients' outcomes were compared by univariate and multivariate analyses. Results: Temporary amenorrhea occurred in 33% of group A patients and 66.7% of group B ( P = 0.01). Premature menopause occurred in 3 patients in group B (0% vs 9%, P = 0.02). Ten patients in group B underwent salvage hysterectomy. Pregnancy desire did not differ between the 2 groups ( P = 0.555). In group A, 57.1% became pregnant; in group B, 36.4% did ( P = 0.060). Instead, pregnancy rate was 52.2% among high-risk patients not undergoing hysterectomy (57.1% vs 52.2%, P = 0.449). There was no difference in miscarriage ( P = 0.479) and premature birth ( P = 0.615) rates. In a multivariate analysis that included age, International Federation of Gynecology and Obstetrics score, chemotherapy type, use of assisted reproductive technologies, previous pregnancies, and pregnancy desire, only age ( P = 0.006) and pregnancy desire ( P = 0.002) had a significant impact on the probability to have subsequent pregnancies. Conclusions: Except for the risk of premature ovarian failure, a rare adverse effect of combined treatments, both single-agent and multiagent chemotherapy can be safely administered to patients with a desire for childbearing. High-risk patients have worse reproductive outcomes because they undergo hysterectomy more frequently than low-risk patients.